PENGARUH GENDER, RELIGIUSITAS DAN SIKAP LOVE OF MONEY PADA PERSEPSI ETIKA PENGGELAPAN PAJAK MAHASISWA AKUNTASI - Basri, Yesi Mutia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 1 (2015), 2015)
This study aims to examine the relationship between gender, religiosity, love of money and the ethics of tax evasion. The population in this study was a student last semester S1 Accounting Department at the University of Riau. The sampling technique used in this study is incidental sampling technique. Data collection was done by distributing questionnaires directly to a sample of students in research. The results of the analysis using the technique with PLS structural equation models showed that the gender effect on religiosity. Gender did not influence the attitude of love of money. Gender had no influence on the ethics of tax evasion. The results show that religiosity has no effect on the ethics of tax evasion. The nature of the love of money or love of money is high then the perceptions of the ethics of tax evasion are also higher. Conversely, this study shows the love of money and religiosity does not mediate the association of gender with the ethics of tax evasion.
Keywords: gender, religiousity, love of money, ethics of tax evasion